Drastic improvement in photoelectrochemical water splitting performance over prolonged reaction time using new carrier-guiding semiconductor nanostructures. Issue 18 (27th April 2022) - Noh, Siyun; Song, Jihoon; Han, Sangmoon; Shin, Jaehyeok; Yu, Yeon-Tae; Kim, Jin Soo
Abstract : Significant improvement in photoelectrochemical water splitting performance with respect to reaction time using new carrier-guiding semiconductor core–shell nanostructures. Abstract : The performance of photoelectrochemical water splitting (PEC-WS) over time was drastically improved using new carrier-guiding semiconductor nanostructures, namely InGaN/GaN core–shell nanowires (CSNWs) with a protruding core, as a photocathode (PC) material. The InGaN/GaN CSNWs designed in this study enable photo-generated electrons to accumulate at the interface between the InGaN core and the GaN shell from where they move toward the upper region of the InGaN/GaN CSNWs, and consequently transfer to the electrolyte. As a result, the PEC-WS performance could be significantly improved. The current density and applied-bias photon-to-current efficiency of the PC were measured to be 28.25 mA cm −2 and 7.07% at −1 and −0.9 V versus a reversible hydrogen electrode, respectively, which are much higher than previously reported values. The current density and hydrogen gas that was generated increased significantly with increasing reaction time and were measured to be 117.04 mA cm −2 and 22.15 mmol cm −2, respectively, after ten hours of PEC-WS. This behavior differs considerably from the significant degradation in the PEC-WS performance over time reported previously. Moreover, the total amount of hydrogen was evaluated as being sufficient to enable the PEC-WS technology to be applied in practice.